(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
Electronic music can arguably be considered the genre that has most effectively encapsulated and articulated human relationships with noise, machines and technology, embodying many technology-oriented concepts. The 21st century has brought about a post-condition that has had an impact on popular electronic music, with the rise of what has been labelled “deconstructed club”, “post-club”, and “conceptronica”. This paper presents a critique of the aforementioned terms, arguing that electronic dance music has consistently employed deconstructive and decontextualizing strategies in relation to pre-existent genres, elements, and expressive codes. Indeed, it is argued that a logic of assemblage and an aesthetic of metamorphosis are intrinsic to popular electronic music, given its technological and recombinant essence. If electronic dance music is based on avantgardist techniques such as assemblage and aesthetic détournement, it may be conceived, then, as an expression of popular avantgarde or popular modernism. Moreover, conceptual underpinnings may be found in popular electronic music since its inception. This paper, therefore, aims to reframe the analysis and discourses on popular electronic music by considering its deconstructive and conceptual aspects, and proposes that the most interesting facets of its recent developments may, in fact, lie elsewhere.